Pengaruh Efikasi Diri terhadap Academic Burnout pada Mahasiswa yang Bekerja di Kota Makassar - Sadaria, Sri Ayu; Razak, Ahmad; Akmal, Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aimed to investigate the effect of self-efficacy on academic burnout among working students in Makassar. This study included 100 working students aged 17 to 25 from Makassar. The measurement instrument were using academic burnout scale and the self-efficacy scale. The sample was collected using the accidental sampling method. This study used a quantitative method with simple regression analysis. The results showed a significant value of 0.000, implying that self-efficacy influences academic burnout among working students in Makassar. The R squared value of 0.184 indicates that self-efficacy contributes 18.4% to academic burnout. The study's implications were to contribute to science development related to academic burnout and slf-efficacy, as well as to serve as a resource for students and educators interested in minimizing academic burnout and enhancing self-efficacy.